2006
DOI: 10.1038/nature04717
|View full text |Cite
|
Sign up to set email alerts
|

Golgi maturation visualized in living yeast

Abstract: The Golgi apparatus is composed of biochemically distinct early (cis, medial) and late (trans, TGN) cisternae. There is debate about the nature of these cisternae. The stable compartments model predicts that each cisterna is a long-lived structure that retains a characteristic set of Golgi-resident proteins. In this view, secretory cargo proteins are transported by vesicles from one cisterna to the next. The cisternal maturation model predicts that each cisterna is a transient structure that matures from early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
366
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(406 citation statements)
references
References 30 publications
33
366
1
6
Order By: Relevance
“…Our data provide further evidence supporting the cisternal progression model of Golgi maturation ( Figure 1G and Supplementary Movie 3). Time required for Golgi cisternae identity change in fission yeast ( Figure 1F) was consistent with maturation dynamics reported previously in S. cerevisiae (Losev et al, 2006;Matsuura-Tokita et al, 2006). As judged by the dynamics of the early Golgi marker protein, Anp1p-mCherry, cis-Golgi cisternae could also arise de novo (Figure 1, E and F, and Supplementary Movie 2), but the relationship of these biogenesis events to tER was more difficult to establish because of the large number of Sec24p-GFP entities.…”
Section: Organization Of the Early Secretory Pathway Compartments In supporting
confidence: 90%
“…Our data provide further evidence supporting the cisternal progression model of Golgi maturation ( Figure 1G and Supplementary Movie 3). Time required for Golgi cisternae identity change in fission yeast ( Figure 1F) was consistent with maturation dynamics reported previously in S. cerevisiae (Losev et al, 2006;Matsuura-Tokita et al, 2006). As judged by the dynamics of the early Golgi marker protein, Anp1p-mCherry, cis-Golgi cisternae could also arise de novo (Figure 1, E and F, and Supplementary Movie 2), but the relationship of these biogenesis events to tER was more difficult to establish because of the large number of Sec24p-GFP entities.…”
Section: Organization Of the Early Secretory Pathway Compartments In supporting
confidence: 90%
“…Compartment maturation by Rab conversion is of special interest for the yeast Golgi complex, because live-cell video microscopy has shown that the yeast Golgi matures in a process analogous to endosome maturation in mammalian cells (9,10). Using live-cell video microscopy, Rivera-Molina and Novick (5) could also detect the conversion of a Ypt1p-enriched Golgi compartment into a Ypt32p-enriched compartment in a process that depended on the Ypt1 GAP, Gyp1p.…”
Section: Compartment Maturation By Rab Conversionmentioning
confidence: 98%
“…By using Rab GEFs and GAPs to generate late Golgi compartments from earlier Golgi compartments, yeast cells ensure vectorial and ordered transport within the secretory pathway. In rapidly growing baker's yeast cells that lack a stacked Golgi complex, Rab interconversion may provide the molecular basis for Golgi maturation in the secretory pathway (9,10). In mammalian cells in which early and late Golgi compartments seem to be more stably stacked, Rab conversion may represent part of the mechanism for vectorial transport, on top of conserved vesicle transfers between individual Golgi compartments.…”
Section: Compartment Maturation By Rab Conversionmentioning
confidence: 99%
“…The yeast TGN appears to be a transient organelle with a half-life of only 1-2 min before it is consumed into many types of vesicles that are targeted to either the plasma membrane, early endosomes, late endosomes, the vacuole, or potentially earlier Golgi cisternae (Losev et al, 2006;Matsuura-Tokita et al, 2006). Thus, TGN residents rely on an active trafficking mechanism to maintain their TGN localization.…”
Section: Discussionmentioning
confidence: 99%